Imagining the future at the global and national scale: a comparative study of British and Dutch press coverage of Rio 1992 and Rio 2012 - Hellsten, Iina; Porter, Amanda; Nerlich, Brigitte (Taylor and Francis, 2014)
Climate change and imagined futures are intricately linked, discussed by policymakers and reported in the media. In this article we focus on the construction of future expectation in the press coverage of the 1992 and 2012 United Nations conferences in Rio de Janeiro in British and Dutch national newspapers. We use a novel combination of methods, semantic co-word networks and metaphor analysis to analyse imagined futures. Our findings show that between 1992 and 2012 there was a switch from future-oriented hope to past-oriented disappointment regarding implementing international agreements on climate change policy. While the UK focused on global issues, the Netherlands focused on national (including colonial) and local ones, reflecting different views and expectations about the future of climate change adaptation and mitigation.